Sustainable Development in Agricultural and Food Supply Chains (Case Study: Coffee Supply Chain in Karo Regency) - Maulidina, Siti Nur; Matondang, Nazaruddin; Tryana S, Meilita (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2024)
One of the most common products grown by many in North Sumatra, especially Karo Regency, is coffee. This plant can bring in foreign exchange, making it a valuable plantation item in the Karo Regency's local economy. Despite the industry's high production and farmers' favorable experiences, soil erosion and water scarcity on agricultural land pose sustainability challenges. This occurs due to farmers needing more technical expertise or real-world post-harvest processing experience. Simultaneously, the Circular Economy (CE) notion is becoming more popular due to its capacity to improve sustainable development. By further utilizing waste to create an alternative product, this research aims to apply CE to the Karo coffee supply chain to increase sustainable elements, specifically social and economic, and lessen its environmental impact. Aside from that, utilizing the Soft System Methodology approach, adjustments must be made to policies or management practices in order to facilitate the deployment of CE. When implementing CE ideas in the agriculture supply chain, Soft System Methodology can help identify issues from the viewpoints of different supply chain actors. The investigation's findings indicate that there is a chance to apply CE to the Karo coffee supply chain. The rise in economic value resulting from utilizing and reprocessing the generated garbage into substitute items is evidence of this, with total sales increasing from Rp 1.130.400.000 to Rp 1.229.350.000 after CE implementation.